Cryptic sulfur cycling in the deep biosphere of ferruginous Lake Towuti, Indonesia - Ruiz-Blas, Fátima; Bartholomäus, Alexander; Henny, Cynthia; Russell, James M.; Kallmeyer, Jens; Vuillemin, Aurèle (Frontiers in Microbiology, 2025)
Lake Towuti, Sulawesi, Indonesia is an ancient tectonic lake, exhibiting iron-rich, sulfate-poor anoxic deep waters. Temporal variations in water column stratification led to sediment accumulation under variable redox conditions. Such ferruginous settings make Lake Towuti an ideal study site to evaluate how a cryptic sulfur cycle could possibly operate under a scarcity of sulfate and abundance of iron minerals, similar to Earth’s primitive oceans. Here, we integrate downcore profiles for pore water geochemistry, reactive iron mineralogy, and bulk sediment elemental composition with microbial cell counts, sulfate reduction rates, 16S rRNA genes and metagenomes to resolve microbial sulfur transformations down to 15 m below lake floor (mblf). Sulfate concentrations and reduction rates dropped within the upper mblf, while pore water ferrous iron increased to its highest concentration down to 3 mblf. Any microbially-produced sulfide precipitated as reduced inorganic sulfur in the sediment, apparently forming authigenic millerite (NiS) during burial. The decrease in cell densities tracked the decline in electron acceptors in pore waters with depth. From 3 to 10 mblf, low but sustained sulfate reduction rates were observed with intermittent presence of nitrate in pore water and increased goethite in the sediment, both acting as potential oxidants of sulfur intermediates. A subsequent re-increase in pore water sulfate occurred in parallel with syntrophic fermentation of volatile fatty acids. Consistent with geochemical evolution, the taxonomic diversity of microbial populations shifted from a bacterial assemblage near the surface to selective but prevailing Bathyarchaeia down to 15 mblf. The corresponding metagenome-assembled genomes predicted metabolic potential for complete sulfate reduction (aprAB, dsrAB) in Thermodesulfovibrionia, whereas Desulfobacterota (incl. Geobacterales, Desulfuromonadales, Syntrophales) and Aminicenantia exhibited versatility in reducing iron, nitrate (narG, napA), nitrite (nirS, nrfA) and sulfate (dsrAB, asrA). By contrast, Bathyarchaeia were predicted to disproportionate sulfur to polysulfides and reduce ferredoxin via electron bifurcation (hyd I-II, sudA, dsrC, dsrE) to fuel a Wood-Ljungdahl pathway, defining homoacetogenesis as terminal electron sink. Together, these mineralogical, geochemical, and metagenomic features provide evidence for a spatially confined but active cryptic sulfur cycle with tight coupling between reduction of mineral ferric iron and intermittent pore water nitrate to syntrophic and lithotrophic (homo)acetogenesis.